Bacteriological Quality in Relation to Sanitation and Hygiene Practices of Tribal Children and Women in Bhadradri Kothagudem District, India - V. Vijaya Lakshmi; M. Milcah Paul (Recent Updates in Disease and Health Research Vol. 2, 2024)
The present study tried to deeply explore the underlying reasons for poor sanitation and hygiene practices of the tribal children and women in the selected tribal areas in India. Sanitation and hygiene are essential for good health and well - being, survival and development of any individual. Tribal women and children may not have proper awareness on the importance of sanitation. Some of the reasons which hinder the development of their awareness levels is due to various issues like lack of education, improper access to basic facilities like water, toilets etc. This is an exploratory study, conducted on 30 tribal women and 30 tribal children residing in the district of Bhadradri Kothagudem, Telangana state, India. The data was collected using an interview questionnaire. Most of the countries are facing challenges in providing minimum sanitation facilities to its people as there are certain factors like population explosion and resource depletion which hinder the provision process. Due to this, people are becoming vulnerable to risks in terms of their health, nutrition and basic survival. In India, there are many interior areas where the tribal population is dominant. Most of them do not follow or maintain basic sanitation and hygiene practices due to various issues like lack of education; gender biased disparities; improper access to basic facilities like water, toilets etc., which effect their well - being, nutritional and health status. The study tried to explore and compare the sanitation, hygiene and nutritional practices of tribal children and women in the district of Bhadradri Kothagudem, Telangana State, India. Some non - Government organizations (NGOs) also can come forward in helping the children and women to understand the importance and benefits of maintaining good sanitation and hygienic practices; and also, on how to improve their nutritional status.